When the grass isn't greener: a case series of young children with accidental marijuana ingestion. Issue 6 (21st July 2015) - Murray, Derek; Olson, Joshua; Lopez, Ana Sofia
Abstract: Marijuana is the most commonly used illicit drug in Canada, with 10% of the general population admitting to its use in the past year. This high prevalence increases risk of accidental ingestion in young children. We report four pediatric cases of accidental marijuana ingestion who presented to our local emergency department with altered mental status. Three patients had extensive testing, including one patient who underwent lumbar puncture and empirical treatment for meningitis. To our knowledge, this is the first Canadian case series since McNabb et al., published over 2 decades ago. The case series aims to highlight the importance of considering acute marijuana intoxication in the differential diagnosis when assessing young children with altered level of consciousness. RÉSUMÉ: La marijuana est la drogue illicite la plus répandue au Canada, et 10 % de la population générale a admis en avoir fait usage au cours de la dernière année. La forte prévalence de la consommation de cette drogue accroît le risque d'ingestion accidentelle chez les jeunes enfants. Seront exposés ici quatre cas d'ingestion accidentelle de marijuana chez des enfants amenés au service local des urgences pour une altération de l'état de conscience. Trois d'entre eux ont été soumis à de nombreux examens, dont l'un à une ponction lombaire et à un traitement empirique en raison d'une possible méningite. Il s'agit, à notre connaissance, de la première série de cas semblables au Canada depuis la publication de l'article de McNabb et de ses collaborateurs il y a plus de 20 ans. La série de cas vise à souligner l'importance d'envisager la possibilité d'une intoxication aiguë à la marijuana dans le diagnostic différentiel d'une altération de l'état de conscience chez de jeunes enfants.